2015
DOI: 10.1007/s12035-015-9389-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Induced Iron Accumulation in Oligodendrocytes Mediates Apoptosis by Eliciting Endoplasmic Reticulum Stress

Abstract: This study was aimed at evaluating the role of increased iron accumulation in oligodendrocytes and its role in their apoptosis in the periventricular white matter damage (PWMD) following a hypoxic injury to the neonatal brain. In response to hypoxia, in the PWM, there was increased expression of proteins involved in iron acquisition, such as iron regulatory proteins (IRP1, IRP2) and transferrin receptor in oligodendrocytes. Consistent with this, following a hypoxic exposure, there was increased accumulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…The underlying mechanisms for iron deposition after ischemia may include the formation of Fe 2+ from degradation of hemoglobin, transportation of Fe 2+ from the damaged blood–brain barrier, and the release of Fe 2+ stimulated by the increase of oxidative stress in the hypoxia state . Increased expressions of iron regulatory proteins and transferrin receptors may also be involved in iron acquisition . Moreover, bulk tissue magnetic susceptibility of white matter can be affected by diamagnetic myelin, which counteracts the effect of tissue iron on the susceptibility value .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms for iron deposition after ischemia may include the formation of Fe 2+ from degradation of hemoglobin, transportation of Fe 2+ from the damaged blood–brain barrier, and the release of Fe 2+ stimulated by the increase of oxidative stress in the hypoxia state . Increased expressions of iron regulatory proteins and transferrin receptors may also be involved in iron acquisition . Moreover, bulk tissue magnetic susceptibility of white matter can be affected by diamagnetic myelin, which counteracts the effect of tissue iron on the susceptibility value .…”
Section: Discussionmentioning
confidence: 99%
“…Once inside cells, iron can catalyze production of highly reactive hydroxyl radicals via the Fenton reaction, which directly damage proteins, DNA and lipids (Winterbourn, 1995). Iron can also induce endoplasmic reticulum stress and apoptosis in cultured hypoxic OLs (Rathnasamy et al, 2016). Thus, assuming the injected iron was initially internalized, direct iron-induced cytotoxicity may have killed local neurons and glia (Bao & Liu, 2004; Liu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Binding of ferritin to iron occurs coincidentally with the formation of myelin in the developing brain and it has been suggested that oligodendrocytes are responsible for regulating iron throughout the CNS [160, 161]. Oxidative stress has been linked to iron dysfunction in oligodendrocytes and, when exposed to hypoxic conditions, iron accumulates inside the cell and induces endoplasmic reticulum (ER) stress and mitochondrial dysfunction resulting in cell death [162]. Likewise, excess levels of iron can result in the formation of hydroxyl radicals, a toxic reactive species implicated in DNA, lipid, and protein disruption [163].…”
Section: Role Of Oligodendroglia In Acute Tissue Inflammationmentioning
confidence: 99%